Implementación de los ejercicios de pliometría para la prevención de lesiones en isquiotibiales en adolescentes de la Escuela de Futbol Semillitas del Cantón Montalvo, periodo octubre 2024 - abril 2025. - Muñoz Triana, Jeanpierre Gregorio (2025)
Preventing injuries in soccer players is a key point in the competition to be able to meet the demands of the game, which is currently a sport that is widely accepted worldwide. Strength and speed are the main point to strengthen the soccer player's lower body in a safe and dynamic way that adapts to the athlete, providing the confidence of obtaining favorable results. The objective of this research was to implement a plyometric exercise plan to avoid hamstring injuries in soccer players from the Semillitas del Cantón Montalvo soccer school. The research study has a descriptive scope. As well as the research is qualitative and quantitative, tools were used to measure the physical condition of the athletes such as the Carmelo Bosco Test and a speed test and after applying the plyometric training, apply the tests again and obtain true results in the research. The data were analyzed using the Excel program. The results obtained at the conclusion of the research are very important since it was possible to establish the importance of well-applied plyometric exercises in soccer players, thus leaving a precedent for future research on plyometrics.